Association of Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis With Marked Improvement in Health‐Related Quality of Life. Issue 2 (29th December 2020) - Maltez, Nancy; Puyade, Mathieu; Wang, Mianbo; Lansiaux, Pauline; Marjanovic, Zora; Charles, Catney; Steele, Russell; Baron, Murray; Colmegna, Ines; Hudson, Marie; Farge, Dominique; ,
Abstract : Objective: To quantify the magnitude, domains, and duration of change in health‐related quality of life (HRQoL) in patients with systemic sclerosis (SSc) who underwent autologous hematopoietic stem cell transplantation (HSCT) as compared to SSc patients with similar characteristics who did not undergo autologous HSCT. Methods: The study was designed as a retrospective study comparing SSc patients who underwent autologous HSCT and SSc patients who met the criteria for transplantation but were treated with conventional care. Outcomes included scores on the 36‐item Short Form (SF‐36) health survey and the Health Assessment Questionnaire (HAQ) and its disease‐specific symptom scales. Differences in scores between the groups were compared using linear models, adjusting for baseline scores and inverse probability of treatment and censoring weights. Results: In total, 41 SSc patients who underwent autologous HSCT and 65 SSc patients treated with conventional care were compared. In marginal linear weighted models, the SF‐36 physical component summary score was a mean ± SEM 7.02 ± 1.94 points higher at the first annual visit ( P = 0.001) and 14.40 ± 6.16 points higher at the seventh annual visit ( P = 0.03) in patients treated with autologous HSCT compared to the conventional care group. HAQ scores were significantly better in the autologous HSCT group compared to the conventional care group during follow‐up (mean ± SEM difference from baseline −0.57 ± 0.13 [ P < 0.001] at the first annual visit and −0.94 ± 0.49 [ P = 0.07] at the seventh annual visit). There were no differences in the SF‐36 mental component summary scores between the 2 groups either at baseline or during follow‐up. Conclusion: This study provides robust complementary HRQoL data, including overall and event‐free survival data, to expand on the standard repertoire of biomedical variables, thus potentially supporting the physical benefits of autologous HSCT in patients with SSc.